The Relationships between Emotional Intelligence and Physical Activity Related to Gender among Undergraduates in the Colombo District - Tharindi Wijerathne; Dina Keumala Sari; Thanuja Liyanage; Lakshika Liyanage (Sumatera Medical Journal, 2025)
Background: Emotions are dynamic aspects of human nature and serve as inspiration for behavior. Higher emotional intelligence (EI) is associated with greater resilience and lower levels of depression. Certain situations can increase physical activity (PA) among young people. This study examined gender differences in EI and PA among undergraduates at State Universities in Colombo District. Objective: To assess how emotional intelligence and physical activity differ between genders in this population. Methods: A descriptive, quantitative, correlational study was conducted with 397 undergraduates who completed the Wong and Low EI questionnaire and the International Physical Activity Questionnaire (IPAQ). Data analysis was performed using the Mann-Whitney U test. Results: Participants were from State Universities in Colombo District, mainly exhibiting moderate to low PA levels. Males showed significantly higher EI than females (z = -3.829, p = .001), while there was no significant difference in PA between genders (z = -.938, p = .348). Conclusion: Males demonstrate higher EI than females, but physical activity levels do not significantly differ by gender. Most participants had low to moderate PA levels, which can inform strategies for preventing non-communicable diseases among youth.